Electrical properties of sol-gel derived PZT/WO3ceramics - Tharathip Sreesattabud (2018)
PZT/xWO3 powders were prepared from the powders synthesized by a modified triol sol-gel method. XRD and TEM results suggested that fully crystallized powders were obtained at the calcination temperature of 600°C for 4 h. A reaction between PZT and WO3 powders seemed more pronounced with increasing WO3 content. To prepare PZT/xWO3 ceramics, the powders were pressed and sintered at 1100°C for 6 h. Phase characterization by XRD indicated that the concentration of WO3 affected lattice parameters and reduced c/a ratios, especially for high content of WO3. SEM images showed that an addition of only 0.5 wt% WO3 significantly decreased grain size of the ceramics. Density of the ceramics, however, did not significantly depend on WO3 concentration below 1 wt%. Addition of suitable amount of WO3 enhanced ferroelectric properties and reduced high-temperature dielectric loss of PZT ceramic. Copyright © Taylor & Francis Group, LLC.